Effect of Leaves of Caesalpinia decapetala on Oxidative Stability of Oil-in-Water Emulsions - Gallego, Maria Gabriela; Skowyra, Monika; Gordon, Michael H.; Nurul Aini, Mohd Azman; Almajano, Maria Pilar (MDPI AG, 2017)
Caesalpinia decapetala (Roth) Alston (Fabaceae) (CD) is used in folk medicine to prevent colds and treat bronchitis. This plant has antitumor and antioxidant activity. The antioxidant effects of an extract from Caesalpinia decapetala (Fabaceae) were assessed by storage of model food oil-in-water emulsions with analysis of primary and secondary oxidation products. The antioxidant capacity of the plant extract was evaluated by the diphenylpicrylhydrazyl (DPPH), Trolox equivalent antioxidant capacity (TEAC), oxygen radical absorbance capacity (ORAC) and ferric reducing antioxidant power (FRAP) assays and by electron paramagnetic resonance (EPR) spectroscopy. Lyophilized extracts of CD were added at concentrations of 0.002%, 0.02% and 0.2% into oil-in-water emulsions, which were stored for 30 days at 33 1 C, and then, oxidative stability was evaluated. The CD extract had high antioxidant activity (700 70 mol Trolox/g dry plant for the ORAC assay), mainly due to its phenolic components: gallic acid, quercetin, catechin, 4-hydroxybenzoic acid and p-coumaric acid. At a concentration of 0.2%, the extract significantly reduced the oxidative deterioration of oil-in-water emulsions. The results of the present study show the possibility of utilizing CD as a promising source of natural antioxidants for retarding lipid oxidation in the food and cosmetic industries.